ANALISIS PROGRAM PELATIHAN DI PUSAT KEGIATAN BELAJAR MASYARAKAT KREATIF - Hasibuan, Jubaidah; Dalimunthe, Khodijah Tussolihi; Manalu, Yeremia Afrianto; Manullang, Thomas Ridoansih; Tamba, Frayogi Benedict (Triwikrama: Jurnal Ilmu Sosial, 2024)
Unemployment is a major challenge in modern society due to the imbalance between the number of workers and employment opportunities as well as limited workforce skills. Non-formal education, such as in Creative PKBM, through the Vocational-Based Package C Equivalency Education program, plays an important role in improving these skills. This research aims to analyze the management innovation of the handicraft training program at PKBM Creative, including planning, material development, implementation, evaluation, and the obstacles faced. With a qualitative descriptive approach, this research uses observation, interviews and documentation techniques for heads of institutions and instructors, and analyzes data using the Miles and Huberman model. The results show that Creative PKBM successfully integrates handicraft training with equality programs through participatory planning, project-based curriculum, and ongoing evaluation. However, there are obstacles in the form of limited resources, facilities and participant involvement. This innovation provides social and economic benefits for participants, but increasing instructor competency, stakeholder support, and use of technology are needed to overcome obstacles and increase program effectiveness. Pengangguran menjadi tantangan utama di masyarakat modern akibat ketidakseimbangan antara jumlah tenaga kerja dan lapangan pekerjaan serta keterbatasan keterampilan tenaga kerja. Pendidikan nonformal, seperti di PKBM Kreatif, melalui program Pendidikan Kesetaraan Paket C Berbasis Vokasi, berperan penting dalam meningkatkan keterampilan tersebut. Penelitian ini bertujuan untuk menganalisis inovasi manajemen program pelatihan kerajinan tangan di PKBM Kreatif, meliputi perencanaan, pengembangan materi, pelaksanaan, evaluasi, serta kendala yang dihadapi. Dengan pendekatan deskriptif kualitatif, Penelitian ini menggunakan teknik observasi, wawancara, dan dokumentasi pada kepala lembaga dan instruktur, serta menganalisis data dengan model Miles dan Huberman. Hasil menunjukkan bahwa PKBM Kreatif berhasil mengintegrasikan pelatihan kerajinan tangan dengan program kesetaraan melalui perencanaan partisipatif, kurikulum berbasis proyek, dan evaluasi berkelanjutan. Namun, terdapat kendala berupa keterbatasan sumber daya, fasilitas, dan keterlibatan peserta. Inovasi ini memberikan manfaat sosial dan ekonomi bagi peserta, namun peningkatan kompetensi instruktur, dukungan stakeholder, dan pemanfaatan teknologi diperlukan untuk mengatasi kendala dan meningkatkan efektivitas program.